Study of Literature Antropology and Education Value in The "Geger Wong Ndekep Macan" Novel of Hari Soemoyo And Their Relevance as a Learning Material of Literature Appreciation - Febriana Fitroh Al Khusna; Edy Suryanto; Djoko Sulaksono (PAEDAGOGIA, 2019)
This study aims to describe: (1) intrinsic and extrinsic structures (2) cultural manifestations (3) the value of character education and (4) the relevance of the Geger Wong Ndekep Macan novel as literary appreciation learning materials in high school. This research is a qualitative descriptive study. Data validation techniques using method triangulation. The results of this study indicate that: (1) the Geger Wong Ndekep Macan novel contains a building structure in the form of solid intrinsic elements including themes, plot, characters and characterizations, place settings, setting time, social settings, perspective, language style, and mandate (2) the form of culture in the novel Geger Wong Ndekep Macan includes cultural ideas, activities and results; (3) Geger Wong Ndekep Macan's novel contains seven types of representations of the value of character education, including the values of empathy, conscience, self-control, respect, kindness, tolerance, and justice; (4) there is the relevance of the novel Geger Wong Ndekep Macan as a material for learning literature appreciation in high school.